ENZYME REPLACEMENT THERAPY IN PATIENTS WITH TYPE 1 GAUCHER DISEASE: A SINGLE-CENTER EXPERIENCE - Golubović, Ivana (Acta medicae Medianae, 2026)
Gaucher disease (GD) is a lysosomal storage disorder inherited in an autosomal recessive pattern. The underlying cause of the disease is a mutation within the gene that encodes the enzyme glucocerebrosidase. Accumulation of glucocerebrosidase within macrophages in the liver, spleen, and bone marrow, and rarely in the lungs and other organs, occurs due to deficient enzyme synthesis, impaired enzyme function, or saposin C deficiency (an enzyme activator). Clinical classification of GD is based on the absence (type 1) or presence (types 2 and 3) of central nervous system manifestations. Levels of β-glucocerebrosidase in leukocytes, as well as the levels of serum chitotriosidase, are measured to establish the definitive diagnosis of GD. Accumulation of β-glucocerebrosidase causes numerous multisystem complications (anemia, thrombocytopenia, hepatomegaly, splenomegaly, skeletal and neurological changes). Since 1991, enzyme replacement therapy (ERT) has been used in the treatment of GD. The study presents treatment outcomes in patients with type 1 GD treated with ERT using taliglucerase alfa at the Clinic of Hematology, Allergology and Clinical Immunology, University Clinical Center Niš. Between January 2016 and January 2025, taliglucerase alfa was administered to five patients with type 1 GD who either did not respond to previous therapy or because the drug donation was discontinued. All patients responded well to treatment, with no reported adverse effects. Administration of taliglucerase alfa resulted in significant improvement of anemia, thrombocytopenia, and organomegaly, as well as improvement in bone status.